2014
DOI: 10.1185/03007995.2014.880049
|View full text |Cite
|
Sign up to set email alerts
|

The Barmer study: impact of standardized warming of the injection site to enhance insulin absorption and reduce prandial insulin requirements and hypoglycemia in obese patients with diabetes mellitus

Abstract: When treating obese patients to target with insulin therapy, use of an injection-site warming device for 3 months resulted in a lower frequency of hypoglycemic events and a reduction in prandial insulin analog requirements. If these results are confirmed in other patient populations, an injection-site warming device may be useful in achieving treatment targets with a safer and more efficient basal bolus therapy in insulin-treated patients with type 1 and type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…All other patients participated in both meal tolerance test procedures. The patients in this sub-study presented with similar characteristics to the patients in the underlying larger real-world study and showed comparable results after 3 months of therapy 11 . They were on intensive insulin treatment only without using additional oral antidiabetic medication.…”
Section: Resultssupporting
confidence: 65%
See 3 more Smart Citations
“…All other patients participated in both meal tolerance test procedures. The patients in this sub-study presented with similar characteristics to the patients in the underlying larger real-world study and showed comparable results after 3 months of therapy 11 . They were on intensive insulin treatment only without using additional oral antidiabetic medication.…”
Section: Resultssupporting
confidence: 65%
“…The prospective real-world Barmer study was conducted from May 2012 to February 2013 with 145 patients 11 . A total of 32 patients were randomized and analyzed for this meal tolerance test sub-study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2004, an oral spray was reported to lower glucose levels when used as a prandial insulin (84). Similarly, in 2004, another company reported proof of concept results for glucose lowering with another oral insulin preparation (85,86).…”
Section: Oral Insulinmentioning
confidence: 96%